"We wouldn't say it to their faces": online harassment, women sports journalists, and feminism. Issue 3 (3rd April 2019) - Antunovic, Dunja
Abstract: In April 2016, a US-based independent sport media organization Just Not Sports launched #MoreThanMean, a digital media campaign to raise awareness about online harassment of women in sports journalism. The video quickly reached 3.7 million views and generated widespread coverage in mainstream news media, sports media, and online-only outlets. Using the #MoreThanMean campaign as a case study, this study assesses how discourses circulate in the sports media environment and, in particular, how feminist messages travel as the content moves from social media to mass media. This study engages with post-feminism in order to examine how various producers of media content position online harassment and sexism in sport and society. While the campaign positioned online harassment as gendered workplace discrimination, the mainstream and sports media coverage typically centralized men in the discussion. Feminist perspectives were constrained to platforms with a progressive, women-centered, and/or explicitly feminist take. Implications for digital feminist activism in the context of sport are discussed.